Interpretation of Tourist Attracion in Japanese Language at Penglipuran Village, Bali - Renold; Buntu Marannu Eppang; Darsyaf Hadi Wijaya; Usman Ode (Politeknik Pariwisata Makassar, Indonesia, 2022)
The research attempts to find out: (1) Personal interpretation in Japanese language by guide at penglipuran village (2) Nonpersonal interpretation in Japanese language by guide at penglipuran village. Interview, documentation and observation were used to meet the purpose of this study integrates with descriptive method. The finding indicates that tour guide who interpretate visitor especially while using Japanese language at Penglipuran village has show very well performance when giving information to the tourist in doing preparation before do guiding such guide flag, uniform, licience, until transferring visitor out of village. A lot of attention at Penglipuran village has been paid for Non-Personal interpretation. Signs and pathway are concerned has meet the appropriate placement, design and clear themes. Tour guide using TORE (Thematic, Organized, Relevant, Enjoyable) method when giving information to the visitors. Guide also use gesture and body language when having problem in interpretating in Japanese language in order to keep communication among the visitors. The using of nonpersonal interpretation media at Penglipuran village are well prepared this can be seen at design, color and them of media, along the information board also written in Japanese language.